Evaluation of Serum Lipid Profile after Different Chemotherapeutic Regimens in Iraqi Patients with Breast Cancer (Indian Journal of Public Health Research & Development, 2020)
Objective: To investigate the effect of doxorubicin, cyclophosphamide and taxane chemotherapy on thelipid profile in Iraqi patients with breast cancer.Method: This cohort prospective study was carried out at the Biochemistry Department, Baghdad Collegeof Medical Sciences, and at the Oncology Clinic, Oncology Teaching Hospital, Baghdad, Iraq, during theperiod from May 2019 to October 2019. It included 56 women with regular menstrual cycle (25-45 years)classified into 3 groups: GI: 29 women with primary breast cancer (before starting chemotherapy), GII:the same 29 women of GI who were finished 4 cycles of anthracycline chemotherapy (course 1) and GIII:which involved another 27 women who had finished both courses of chemotherapy, (course 1) and 4 cyclesof taxanes (course 2). Serum cholesterol, LDL, HDL and TG were measured using colorimetric method.Results: The results of the present study showed that the (mean±SEM) of the serum cholesterol wasdecreased significantly (p
Keywords: Breast cancer, chemotherapy, cholesterol, HDL, LDL, TG